Elderly activity recognition using smartphones and wearable devices - Zimmermann, Larissa Cardoso (2019)
Research that involves human-beings depends on the data collection. As technology solutions become popular in the context of healthcare, researchers highlight the need for monitoring and caring patients in situ. Human Activity Recognition (HAR) is a research field that combines two areas: Ubiquitous Computing and Artificial Intelligence. HAR is daily applied in several service sectors including military, security (surveillance), health and entertainment. A HAR system aims to identify and recognize the activities and actions a user performs, in real time or not. Ambient sensors (e.g. cameras) and wearable devices (e.g. smartwatches) collect information about users and their context (e.g. localization, time, companions). This data is processed by machine learning algorithms that extract information and classify the corresponding activity. Although there are several works in the literature related to HAR systems, most studies focusing on elderly users are limited and do not use, as ground truth, data collected from elder volunteers. Databases and sensors reported in the literature are geared towards a generic audience, which leads to loss in accuracy and robustness when targeted at a specific audience. Considering this gap, this work presents a Human Activity Recognition system and corresponding database focusing on the elderly, raising requirements and guidelines for supportive HAR system and the selection of sensor devices. The system evaluation was carried out checking the accuracy of the activity recognition process, defining the best statistical features and classification algorithms for the Elderly Activity Recognition System (EARS). The results suggest that EARS is a promising supportive technology for the elderly, having an accuracy of 98.37% with KNN (k = 1).